Responses of Pearl Oysters to Marine Heatwaves as Indicated by HSP70 - Xu, Yang; Liang, Jian; He, Guixiang; Liu, Xiaolong; Yang, Ke; Masanja, Fortunatus; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2022)
Marine heatwaves (MHWs) can severely affect bivalves and ecosystems they support. Heat shock proteins (HSPs) are a group of molecular chaperones playing a critical role in the cellular protection and thermotolerance and thereby constraining physiological responses of marine bivalves to MHWs. Here, we cloned the full-length HSP70 cDNA from the Pinctada maximal (PmHSP70) and evaluated the expression of PmHSP70 in pearl oysters under acute and repeatedly-occurring MHWs conditions. The full-length of PmHSP70 is 2474 bp, containing an ORF of 1956 bp encoding 655 amino acids with a predicted molecular weight of 71.23 kDa and 5.26 theoretical isoelectric point. Under the scenario of acute MHWs, the expression of PmHSP70 was significantly highly expressed at 32°C and 36°C, and reached the highest at 12h and 72h, respectively, indicating that pearl oysters rapidly up-regulated the expression of HSP70 in response to MHWs. In the repeatedly-occurring MHWs scenario, the thermal response of pearl oysters was alleviated, as best exemplified by significantly lowered expression levels of PmHSP70. Therefore, we speculate that long-term and repeated MHWs can alleviate the thermal stress of pearl oyster. This finding is encouraging and will provide us with meaningful insights into the acclimation of marine bivalves to extreme environments in the future.